“Do not look at me like that”: Is the facial expression score reliable and accurate to evaluate pain in large domestic animals? A systematic review - Fischer-Tenhagen, Carola; Meier, Jennifer; Pohl, Alina (Frontiers in Veterinary Science, 2022)
Facial expression scoring has proved to be useful for pain evaluation in human patients. In the last ten years, equivalent scales have been developed for various animal species including large domestic animals. The research question of this systematic review was: Is facial expression scoring (intervention) a valid by adapting the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) checklist. The search strategy extracted 30 articles, with a main share on equids, but considerable numbers include cows, pigs and sheep. Most studies evaluated facial action units (FAUs) including the eye region, orbital region, cheek or chewing muscles, lips, mouth and the position of the ears. Inter - observer reliability was tested in 21 studies. Overall FAU reliability was substantial, but there were differences for individual FAUs. Position of the ear had almost perfect inter-observer reliability (inter-class coefficient 0.73 – 0.97). Validity was tested in five studies with reported accuracy values ranging from 68.2 to 80.0%. The systematic review revealed that facial expression scores are an easy way to learn and reliable test to identify an animal in pain or distress. Many studies were lacking a reference standard and a true control group. Further research is warranted, to evaluate test accuracy of facial expression scoring as a live pen side test.method to evaluate pain (outcome) in large domestic animals (population)? We searched two databases for relevant articles using the search string: “grimace scale” OR “facial expression” AND animal OR “farm animal” NOT mouse NOT rat NOT “laboratory animal”. Risk of bias was estimated